Conjungtival Impression Cytology (CIC)In Diarrheal Children In Pediatrics Department ofM. Djamil General Hospital, Padang — Indonesia Preliminary Report - Iwan Djasananda; Hafid Ardy (Indonesian Association of Food Technologists, 2003)
Digestive system infection such as diarrhea might cause malabsorbtion and low intake of vitamin A or reverse. Vitamin A deficiency may result an increase in mortality rate. This study was performed to observe the picture of the Conjunctival Impression Cytology (CIC) in children suffers acutely from diarrhea. Methods: Patient's age were between 2-7 years old, and hospitalized because of diarrhea at the pediatrics Department of M Djamil General Hospital, Padang, between March and April 2003. Patients nutritional state were evaluated using Height, Weight and Age parameters as compared to standard (WHO) table. CIC test were done according to Tseng method. Examinations were done on the first day of hospitalization. Nutritional state, CIC picture were statistically analyzed. CIC examination, were done on 22 eye of patients suffering from diarrhea, and as a control from 16 eye. Result: In diarrhea group, the result of CIC examination was statistically significant different from that found in control group. But the nutritional state, frequency of diarrhea in a year, and duration of the diarrhea didn 't showed a statistical significance. Further study might be needed with on a larger number of cases and longer duration of diarrhea. Conclusion: CIC examinations are a simple test that could be used to detect vitamin A deficiency in diarrhea patients.